Does dietary linseed or canola oil affect lipid metabolism, immunity, and n-3 polyunsaturated fatty acids content in quail eggs? - Nahed S.H. Abo Egila; Waleed M. Dosoky; Najat S.M. Khisheerah; Mohamed H. Ahmed; Soliman M. Zahran; Najlaa H. Almohmadi; Wafaa F. Abusudah; Mahmoud Kamal; Mahmoud Moustafa; Guillermo Tellez-Isaias; Mohammed Al-Shehri; Mohamed E. Abd El-Hack (Poultry Science, 2023)
ABSTRACT: One of the most intriguing areas of research and innovation in the animal production and food sector recently has been designed-enriched products. These items are regarded as functional foods because they feature components that have advantageous physiological impacts on human health. In the production of poultry, designed eggs constitute a significant category of functional foods. The present study hypothesized that adding different kinds of oils to quail diets will help produce designer eggs rich in omega-3 and 6 fatty acids in addition to enhancing productive performance. So, this study examined how linseed (flaxseed) and canola oils with various levels can affect lipid metabolism, immune function, and the amount of n-3 polyunsaturated fatty acids (n-3 PUFA) in Japanese quail eggs. This work was conducted using 3 different vegetable oils (sunflower, linseed, and canola oils) and 3 different antioxidant supplements (0, 250 mg vitamin E/kg feed, and 1,000 mg ginger/kg feed) in a 3 × 3 factorial experiment. When linseed or canola oil was added to the diet, the number of fatty acids in the egg yolks of Japanese quail layers fell by (12.7 and 18.9%) and (41.4 and 24.6%), respectively. The amounts of saturated and monounsaturated fatty acids in total eggs fell by 21.9 and 14.6% and 24.5 and 15.8%, respectively, at 20 wk of age. However, when linseed and canola oil were added to the diet, the sum n-3 PUFA content in the egg yolk of Japanese quail-laying hens was noticeably raised at 15 and 20 wk of age. At 15 and 20 wk of age, the same groups' total n-6 PUFA content considerably increased compared to the group that did not receive flaxseed. In conclusion, during the laying period of Japanese quail, linseed oil, canola oil, vitamin E, or ginger positively affected productivity, blood hematology, constituents, resistance, lipid digestion system, and antioxidative properties in serum and egg yolk.